ChemInform Abstract: Copper‐Catalyzed Highly Regioselective 2‐Aryloxylation of 2, x‐Dihalopyridines. Issue 22 (13th May 2013) - Zhou, Qizhong; Zhang, Bin; Du, Tieqi; Gu, Haining; Ye, Yuyuan; Jiang, Huajiang; Chen, Rener
Abstract The title reaction is achieved for the first time.